Power cable flame-retardant sheath tube and preparation method thereof
The preparation of the power cable flame retardant sheathed casing through the three-layer co-extrusion process solves the problems of insufficient flame retardancy and poor fire resistance at high temperatures in the prior art, and achieves efficient flame retardant and fire resistance.
Patent Information
- Application Number
- CN202510030892.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The existing cable flame retardant sheaths have problems with insufficient flame retardancy and poor fire resistance under continuous action of high temperature.
The power cable flame retardant sheath is prepared by a three-layer co-extrusion process. The inner layer material is composed of matrix resin and nanofiller, the intermediate layer material is added with expanded graphite and inorganic flame retardant, and the outer layer material is composed of ceramicable silicone rubber and nanoceramic powder.
It significantly improves flame retardancy and fire resistance, can maintain excellent flame retardancy at high temperatures, with fire resistance reaching more than 30 minutes and flame retardancy reaching UL94V-0 level.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cable sheath materials, and in particular to a flame retardant sheath tube for power cables and a preparation method thereof. Background Art
[0002] With the rapid development of the power industry, power cables, as an important carrier of energy transmission, are increasingly used in increasingly complex scenarios, and the performance requirements for cable materials are constantly increasing. Especially in high temperature, flammable or chemically corrosive environments, power cables must have excellent flame retardant properties, mechanical properties and chemical corrosion resistance to ensure the safe and stable operation of the power system. As an important component of power cables, flame retardant sheaths not only protect the cable body from damage by the external environment, but also play a flame retardant and protective role under extreme conditions such as fire.
[0003] In the prior art, cable flame retardant sheath tubes are usually prepared by adding inorganic flame retardants. A high proportion of inorganic flame retardants is added to the matrix resin, and the flame retardant sheath tubes are prepared by melt blending, extrusion molding and other processes to achieve flame retardancy and thermal stability of the sheath tubes.
[0004] Regarding the above technical solution, although the flame retardant performance can be improved by adding a high proportion of inorganic flame retardants and it can play a certain protective role under conventional fire conditions, there are still problems of insufficient flame retardancy and poor fire resistance under the continuous action of high temperature. Summary of the invention
[0005] In order to improve the problems of insufficient flame retardancy and poor fire resistance under continuous high temperature, the present application provides a flame retardant sheath tube for power cables and a preparation method thereof.
[0006] The invention provides a flame-retardant sheath tube for a power cable, the sheath tube comprising three layers, each layer being made of the following raw materials in parts by weight: inner layer material: 80-100 parts of a matrix resin; 1-5 parts of a nano filler; middle layer material: 50-70 parts of a copolymer resin; 20-40 parts of expanded graphite; 30-50 parts of an inorganic flame retardant; outer layer material: 80-90 parts of a ceramicized organic silicon rubber; and 5-15 parts of a nano ceramic powder.
[0007] As a preferred embodiment, the matrix resin is selected from one of cross-linked polyethylene, low-density polyethylene and linear low-density polyethylene.
[0008] As a preferred embodiment, the nanofiller is selected from one or a combination of at least two of nanographene oxide and nanomontmorillonite.
[0009] As a preferred embodiment, the copolymer resin is ethylene-vinyl acetate copolymer, wherein the vinyl acetate content is 14%-28%.
[0010] As a preferred embodiment, the expanded graphite is an expanded graphite with a particle size of 300-500 meshes.
[0011] As a preferred embodiment, the inorganic flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:1.
[0012] As a preferred embodiment, the ceramicizable silicone rubber is a vinyl-containing silicone rubber.
[0013] As a preferred embodiment, the nano ceramic powder is selected from one of organic montmorillonite nano sheets, nano silicon dioxide and nano alumina.
[0014] The present application also provides a method for preparing a flame-retardant sheath tube for a power cable, the method comprising the following steps: preparation of an inner layer material: placing a base resin in a dryer for drying to obtain a dried base resin; placing a nanofiller and 0.5-2 parts of polyethylene glycol or polyvinyl pyrrolidone measured by weight into an ultrasonic disperser, using ethanol as a medium for ultrasonic dispersion for 30-60 minutes, placing the dispersed nanofiller in a vacuum drying oven for drying to constant weight to obtain a pretreated nanofiller; adding the dried base resin and the pretreated nanofiller to a twin-screw extruder, and performing melt blending and extrusion in the twin-screw extruder to obtain an inner layer material; preparation of an intermediate layer material: placing expanded graphite and an inorganic flame retardant in a high-speed mixer for mixing to obtain a flame retardant mixture; placing a copolymer resin in a vacuum drying oven for drying to obtain a dried copolymer resin; mixing the dried copolymer resin, the flame retardant mixture, and hindered phenol measured by weight 0.2-0.5 parts of antioxidant are added to a twin-screw extruder for melt blending and extrusion to obtain an intermediate layer material; preparation of an outer layer material: grinding nano ceramic powder in a ball mill to obtain pretreated nano ceramic powder; adding ceramicizable silicone rubber, pretreated nano ceramic powder and 0.2-0.5 parts of hindered phenol antioxidant measured by weight to an open mill for mixing to obtain an outer layer material; three-layer co-extrusion molding: adding an inner layer material, an intermediate layer material and an outer layer material to different feed ports of a three-layer co-extrusion extruder respectively, melting in the three-layer co-extrusion extruder, and synchronously extruding through a three-layer co-extrusion die head of the three-layer co-extrusion extruder according to a preset extrusion ratio of the inner layer material, the intermediate layer material and the outer layer material to form a three-layer co-extruded tubular sheath; introducing the three-layer co-extruded tubular sheath into a cooling water tank, controlling the water temperature at 15-25°C, cooling and shaping, and then towing through a towing device, cutting into a required length, to obtain a finished flame-retardant sheath pipe of a power cable.
[0015] As a preferred solution, the preset extrusion ratio of the inner layer material, the middle layer material and the outer layer material is 1:2:1.
[0016] Compared with the prior art, the present application has the following beneficial effects: strong flame retardancy and good fire resistance. The inner layer material is prepared by ultrasonic dispersion and melt blending of matrix resin and nanofiller, which improves the mechanical strength and thermal stability of the material; the middle layer material is prepared by adding expanded graphite and inorganic flame retardant to the mixed treatment, which significantly improves the flame retardant performance; the outer layer material is realized by blending nano-ceramic powder and ceramic silicone rubber, so that the material has high temperature protection and structural stability; the three materials are integrated into a three-layer co-extrusion process, and the flame-retardant sheath of the power cable of the required length is obtained by cooling and sizing, which improves the problem of insufficient flame retardancy and poor fire resistance under the continuous action of high temperature. DETAILED DESCRIPTION
[0017] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0018] Embodiment 1: This embodiment provides a flame retardant sheath tube for a power cable, comprising the following raw material components in parts by weight: Cross-linked polyethylene: 90 parts; Nano graphene oxide: 2 parts; Ethylene-vinyl acetate copolymer (vinyl acetate content 14%): 60 parts; Expanded graphite (300 mesh): 30 parts; Inorganic flame retardant (magnesium hydroxide and aluminum hydroxide, weight ratio 1:1): 40 parts; Ceramicizable silicone rubber (vinyl-containing silicone rubber): 85 parts; Organic montmorillonite nanosheets: 10 parts.
[0019] Preparation method: Preparation of inner layer material: placing the cross-linked polyethylene in a dryer and drying it at 90° C. for 3 hours to obtain dry cross-linked polyethylene; Nano-graphene oxide and 0.5 parts of polyethylene glycol measured by weight are added to an ultrasonic disperser, and ultrasonic treatment is performed in the ultrasonic disperser using ethanol as a medium for 40 minutes. The dispersed nano-graphene oxide is placed in a vacuum drying oven and dried at 75° C. to constant weight to obtain pretreated nano-graphene oxide.
[0020] The dried cross-linked polyethylene and the pretreated nano-graphene oxide are added to a twin-screw extruder, and the temperature in the twin-screw extruder is set to 140°C, the screw speed is 120 rpm, and the dried cross-linked polyethylene, the pretreated nano-graphene oxide and the polyethylene glycol are melt-blended and extruded, and pelletized after cooling to obtain the inner layer material. The addition of polyethylene glycol is used to improve the dispersibility of the nano-graphene oxide in the cross-linked polyethylene.
[0021] Preparation of intermediate layer materials: The 300-mesh expanded graphite and the inorganic flame retardant were placed in a high-speed mixer and mixed for 5 minutes to obtain a flame retardant mixture.
[0022] The ethylene-vinyl acetate copolymer having a vinyl acetate content of 14% was then placed in a vacuum drying oven and dried at 70° C. for 3 hours to obtain a dried ethylene-vinyl acetate copolymer.
[0023] The dried ethylene-vinyl acetate copolymer, the flame retardant mixture and 0.2 parts of the hindered phenolic antioxidant measured by weight are added to a twin-screw extruder, and the temperature in the twin-screw extruder is set to 110° C. and the screw speed is 120 rpm. The dried ethylene-vinyl acetate copolymer, the flame retardant mixture and the hindered phenolic antioxidant are melt-blended and extruded, and pelletized after cooling to obtain an intermediate layer material. The hindered phenolic antioxidant is added to prevent thermal degradation of the intermediate layer material.
[0024] Preparation of outer layer material: The organic montmorillonite nanosheets were put into a ball mill and ground for 2 hours to obtain organic montmorillonite nanopowders.
[0025] The ceramicized organic silicone rubber, organic montmorillonite nanopowder and 0.5 parts of hindered phenolic antioxidant measured by weight are added to an open mill, and the mixing temperature is set to 40° C. and the mixing time is set to 20 minutes in the open mill to mix the ceramicized organic silicone rubber, organic montmorillonite nanopowder and hindered phenolic antioxidant to obtain an outer layer material. The hindered phenolic antioxidant is added to prevent thermal degradation of the outer layer material.
[0026] Co-extrusion: The inner layer material, the middle layer material and the outer layer material are respectively added into different feed ports of the three-layer co-extrusion extruder, and the heating temperature of the inner layer material port is set to 140°C to heat the inner layer material, the heating temperature of the middle layer material port is set to 160°C to heat the middle layer material, and the heating temperature of the outer layer material port is set to 120°C to heat the outer layer material, and then they are extruded together to form a three-layer co-extruded tubular sheath.
[0027] The three-layer co-extruded tubular sheath is introduced into the cooling water tank with the water temperature controlled at 15°C. After cooling and shaping, it is towed by a traction device. The traction speed should match the extrusion speed and be set to 5m / min to ensure that the sheath wall thickness is uniform and there is no tensile deformation. It is then cut into preset lengths to obtain a finished flame-retardant sheath for power cables.
[0028] Test results: The flame retardant sheath tube maintains excellent flame retardant properties at a high temperature of 150°C. Its fire resistance shows no droplet phenomenon within 30 minutes, and the structure remains intact. The flame retardant performance is UL94V-0 grade. The heat-resistant breakdown performance shows that the dielectric strength retention rate is 95% at 150°C.
[0029] Example 2 This embodiment provides a flame retardant sheath tube for a power cable, comprising the following raw material components in parts by weight: Low density polyethylene: 95 parts; Nano-montmorillonite: 3 parts; Ethylene-vinyl acetate copolymer (vinyl acetate content 20%): 65 parts; Expanded graphite (400 mesh): 25 parts; Inorganic flame retardant (magnesium hydroxide and aluminum hydroxide, weight ratio 1:1): 35 parts; Ceramicizable silicone rubber: 87 parts; Nano-alumina: 8 parts.
[0030] Preparation method: Preparation of inner layer material: The low-density polyethylene was placed in a dryer and dried at 80° C. for 4 hours to obtain dry low-density polyethylene; Nano-montmorillonite and 1 part of polyvinyl pyrrolidone measured by weight are added to an ultrasonic disperser, and ultrasonic treatment is carried out for 30 minutes using ethanol as a medium in the ultrasonic disperser. The dispersed nano-montmorillonite is placed in a vacuum drying oven and dried at 60° C. to constant weight to obtain pretreated nano-montmorillonite.
[0031] The dried low-density polyethylene and the pretreated nano-montmorillonite are added to a twin-screw extruder. In the twin-screw extruder, the temperature is set to 150°C and the screw speed is 130 rpm. The dried low-density polyethylene, the pretreated nano-montmorillonite and polyvinyl pyrrolidone are melt-blended and extruded, and pelletized after cooling to obtain the inner layer material. The addition of polyvinyl pyrrolidone is used to improve the dispersibility of nano-graphene oxide in cross-linked polyethylene.
[0032] Preparation of intermediate layer materials: The 400-mesh expanded graphite and the inorganic flame retardant were placed in a high-speed mixer and mixed for 7 minutes to obtain a flame retardant mixture.
[0033] The ethylene-vinyl acetate copolymer having a vinyl acetate content of 20% was then placed in a vacuum drying oven and dried at 80° C. for 2 hours to obtain a dried ethylene-vinyl acetate copolymer.
[0034] The dried ethylene-vinyl acetate copolymer, the flame retardant mixture and 0.5 parts of the hindered phenolic antioxidant measured by weight are added to a twin-screw extruder, and the temperature in the twin-screw extruder is set to 110° C. and the screw speed is 120 rpm. The dried ethylene-vinyl acetate copolymer, the flame retardant mixture and the hindered phenolic antioxidant are melt-blended and extruded, and pelletized after cooling to obtain an intermediate layer material. The hindered phenolic antioxidant is added to prevent thermal degradation of the intermediate layer material.
[0035] Preparation of outer layer material: The nano-alumina was put into a ball mill and ground for 3 hours to obtain nano-alumina powder.
[0036] The ceramic organic silicone rubber, nano-alumina powder and 0.3 parts of hindered phenolic antioxidant measured by weight are added to an open mill, and the mixing temperature is set to 50° C. and the mixing time is set to 15 minutes in the open mill to mix the ceramic organic silicone rubber, nano-alumina powder and hindered phenolic antioxidant to obtain an outer layer material. The hindered phenolic antioxidant is added to prevent thermal degradation of the outer layer material.
[0037] Co-extrusion: The inner layer material, the middle layer material and the outer layer material are respectively added into different feed ports of the three-layer co-extrusion extruder, and the heating temperature of the inner layer material port is set to 150°C, the heating temperature of the middle layer material port is set to 160°C to heat the middle layer material, and the heating temperature of the outer layer material port is set to 120°C to heat the outer layer material, and then they are extruded together to form a three-layer co-extruded tubular sheath.
[0038] The three-layer co-extruded tubular sheath is introduced into the cooling water tank with the water temperature controlled at 15°C. After cooling and shaping, it is towed by a traction device. The traction speed should match the extrusion speed and be set to 7m / min to ensure that the sheath wall thickness is uniform and there is no tensile deformation. It is then cut into preset lengths to obtain a finished flame-retardant sheath for power cables.
[0039] Test results: The flame retardant sheath tube maintains excellent flame retardant properties at a high temperature of 140°C. Its fire resistance shows no obvious deformation within 25 minutes and no molten droplets. Its flame retardant performance is UL94V-0 grade. Its heat-resistant breakdown performance shows a dielectric strength retention rate of 92% at 140°C.
[0040] Example 3 This embodiment provides a flame retardant sheath tube for a power cable, comprising the following raw material components in parts by weight: Linear low density polyethylene: 100 parts; Mixed nanofiller (nanographene oxide and nanomontmorillonite mixed in a ratio of 1:1): 4 parts; Ethylene-vinyl acetate copolymer (vinyl acetate content 28%): 55 parts; Expanded graphite (500 mesh): 20 parts; Inorganic flame retardant (magnesium hydroxide and aluminum hydroxide, weight ratio 1:1): 30 parts; Ceramicizable silicone rubber: 90 parts; Nano silicon dioxide: 12 parts.
[0041] Preparation method: Preparation of inner layer material: placing the linear low-density polyethylene in a dryer and drying it at 80° C. for 4 hours to obtain a dry linear low-density polyethylene; The mixed nanofiller and 1 part of polyethylene glycol measured by weight are added into an ultrasonic disperser, and ultrasonic treatment is performed in the ultrasonic disperser using ethanol as a medium for 50 minutes. The dispersed mixed nanofiller is placed in a vacuum drying oven and dried at 80° C. to constant weight to obtain a pretreated mixed nanofiller.
[0042] The dried linear low-density polyethylene and the pretreated mixed nanofiller are added to a twin-screw extruder, and the twin-screw extruder is used to extrude into granules at 130° C. to obtain an inner layer material. The addition of polyethylene glycol is used to improve the dispersibility of nano-graphene oxide in cross-linked polyethylene.
[0043] Preparation of intermediate layer materials: The 500-mesh expanded graphite and the inorganic flame retardant were placed in a high-speed mixer and mixed for 5 minutes to obtain a flame retardant mixture.
[0044] The ethylene-vinyl acetate copolymer having a vinyl acetate content of 28% was then placed in a vacuum drying oven and dried at 90° C. for 3 hours to obtain a dried ethylene-vinyl acetate copolymer.
[0045] The dried ethylene-vinyl acetate copolymer, the flame retardant mixture and 0.4 parts of the hindered phenolic antioxidant measured by weight are added to a twin-screw extruder, and the temperature in the twin-screw extruder is set to 110° C. and the screw speed is 120 rpm. The dried ethylene-vinyl acetate copolymer, the flame retardant mixture and the hindered phenolic antioxidant are melt-blended and extruded, and pelletized after cooling to obtain an intermediate layer material. The hindered phenolic antioxidant is added to prevent thermal degradation of the intermediate layer material.
[0046] Preparation of outer layer material: The nano-silicon dioxide was put into a ball mill and ground for 2 hours to obtain nano-silicon dioxide powder.
[0047] The ceramic silicone rubber, nano-silica powder and 0.5 parts of hindered phenolic antioxidant measured by weight are added to an open mill, and the mixing temperature is set to 50° C. and the mixing time is set to 15 minutes in the open mill to mix the ceramic silicone rubber nano-silica powder and the hindered phenolic antioxidant to obtain an outer layer material. The hindered phenolic antioxidant is added to prevent thermal degradation of the outer layer material.
[0048] Co-extrusion: The inner layer material, the middle layer material and the outer layer material are respectively added into different feed ports of the three-layer co-extrusion extruder, and the heating temperature of the inner layer material port is set to 140°C to heat the inner layer material, the heating temperature of the middle layer material port is set to 160°C to heat the middle layer material, and the heating temperature of the outer layer material port is set to 120°C to heat the outer layer material, and then they are extruded together to form a three-layer co-extruded tubular sheath.
[0049] The three-layer co-extruded tubular sheath is introduced into the cooling water tank with the water temperature controlled at 15°C. After cooling and shaping, it is towed by a traction device. The traction speed should match the extrusion speed and be set to 10m / min to ensure that the wall thickness of the sheath is uniform and there is no tensile deformation. It is then cut into preset lengths to obtain a finished flame-retardant sheath for power cables.
[0050] Test results: The flame retardant sheath tube maintains excellent flame retardant properties at a high temperature of 155°C. Its fire resistance reaches 35 minutes without any droplets and obvious cracks on the tube wall. Its flame retardant performance is UL94V-0 grade. Its heat-resistant breakdown performance has a dielectric strength retention rate of 94% at 155°C.
[0051] Comparison 1: Same as Example 1, but without adding nanofiller.
[0052] Test results: The flame retardant sheath pipe cannot maintain integrity at a high temperature of 130°C. Molten droplets appear after only 2 minutes of fire resistance, and the pipe wall completely fails. The flame retardant performance is gradeless. The dielectric strength retention rate of the heat-resistant breakdown performance at 130°C is 75%.
[0053] Comparison 2: Same as Example 1, but without adding expanded graphite.
[0054] Test results: The fire resistance of the flame retardant sheath pipe is reduced at a high temperature of 135°C, and obvious molten droplets appear after only 10 minutes; the flame retardancy is UL94V-2 level; the heat-resistant breakdown performance has a dielectric strength retention rate of 78% at 135°C.
[0055] Comparison 3: The same as Example 1, but without adding nano ceramic powder.
[0056] Test results: The flame retardant sheath has average fire resistance at 140°C, with only a small amount of molten droplets appearing after 15 minutes; the flame retardant performance is UL94V-1; the heat-resistant breakdown performance has a dielectric strength retention rate of 80% at 140°C.
[0057] Comparison 4: The same as Example 1, but without adding the ceramicizable silicone rubber.
[0058] Test results: The fire resistance of the flame retardant sheath pipe decreases at a high temperature of 135°C, and only lasts for 20 minutes, with obvious molten droplets appearing; the flame retardancy is UL94V-2 level; the heat-resistant breakdown performance has a dielectric strength retention rate of 77% at 135°C.
[0059] The performance tests were conducted on the flame retardant sheath materials of power cables of Examples 1 to 3 and Comparative Examples 1 to 4. The results are shown in Table 1 below: Table 1: Test result analysis: Examples 1-4 all reached UL94V-0 grade, showing excellent flame retardant properties, while the flame retardant properties of the comparisons were significantly reduced, with the lowest being no grade (Comparison 1).
[0060] The fire resistance time of the embodiment is more than 25 minutes, and can reach up to 35 minutes (Example 3). In the comparison group, the shortest fire resistance time is only 2 minutes (Comparison 1), which shows the important role of key materials such as nanofillers and expanded graphite. The dielectric strength retention rate of the embodiment is more than 92%, while the lowest in the comparison group is only 75% (Comparison 1).
[0061] The test results of Examples 1 to 3 show that the synergistic effect of different functional layer materials in the three-layer co-extruded sheath tube significantly improves the overall performance, especially in terms of flame retardancy, fire resistance and heat breakdown resistance, which is much better than the control example.
[0062] Comparisons 1 to 4 verify the contribution of nanofillers, expanded graphite, nanoceramic powder and ceramic silicone rubber to performance improvement.
[0063] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A flame retardant sheath tube for power cables, characterized in that: The sheath tube comprises three layers, each layer being made of the following raw materials in parts by weight: Inner Material: 80-100 parts of base resin; 1-5 parts of nanofiller; Middle layer material: 50-70 parts of copolymer resin; Expanded graphite 20-40 parts; 30-50 parts of inorganic flame retardant; Outer Material: 80-90 parts of ceramic silicone rubber; 5-15 parts of nano ceramic powder.
2. The flame retardant sheath tube for power cables according to claim 1, characterized in that: The matrix resin is selected from one of cross-linked polyethylene, low-density polyethylene and linear low-density polyethylene.
3. The flame retardant sheath tube for power cables according to claim 1, characterized in that: The nano filler is selected from one of nano graphene oxide and nano montmorillonite or a combination of at least two thereof.
4. The flame retardant sheath tube for power cables according to claim 1, characterized in that: The copolymer resin is ethylene-vinyl acetate copolymer, wherein the vinyl acetate content is 14%-28%.
5. The flame retardant sheath tube for power cables according to claim 1, characterized in that: The expanded graphite is an expanded graphite with a particle size of 300-500 meshes.
6. The flame retardant sheath tube for power cables according to claim 1, characterized in that: The inorganic flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:
1.
7. The flame retardant sheath tube for power cables according to claim 1, characterized in that: The ceramicizable organic silicone rubber is an organic silicone rubber containing vinyl.
8. The flame retardant sheath tube for power cables according to claim 1, characterized in that: The nano ceramic powder is selected from one of organic montmorillonite nano sheets, nano silicon dioxide and nano aluminum oxide.
9. A method for preparing the flame-retardant sheath tube of a power cable according to claims 1-8, characterized in that: The preparation method comprises the following steps: Preparation of inner layer material: placing the base resin in a dryer for drying to obtain a dried base resin; Place the nanofiller and 0.5-2 parts of polyethylene glycol or polyvinyl pyrrolidone measured by weight into an ultrasonic disperser, use ethanol as a medium for ultrasonic dispersion for 30-60 minutes, place the dispersed nanofiller in a vacuum drying oven and dry to constant weight to obtain a pretreated nanofiller; Adding the dried base resin and the pretreated nanofiller into a twin-screw extruder, and performing melt blending and extrusion in the twin-screw extruder to obtain an inner layer material; Preparation of intermediate layer materials: The expanded graphite and the inorganic flame retardant are placed in a high-speed mixer for mixing to obtain a flame retardant mixture; placing the copolymer resin in a vacuum drying oven to dry it, thereby obtaining a dried copolymer resin; Adding the dried copolymer resin, the flame retardant mixture and 0.2-0.5 parts by weight of a hindered phenol antioxidant into a twin-screw extruder for melt blending and extrusion to obtain an intermediate layer material; Preparation of outer layer material: The nano-ceramic powder is put into a ball mill and ground to obtain pre-treated nano-ceramic powder; The ceramic silicone rubber, the pretreated nano-ceramic powder and 0.2-0.5 parts by weight of the hindered phenol antioxidant are added to an open mill for mixing to obtain an outer layer material; Three-layer co-extrusion molding: The inner layer material, the middle layer material and the outer layer material are respectively added to different feed ports of the three-layer co-extrusion extruder, and after being melted in the three-layer co-extrusion extruder, they are synchronously extruded by using a three-layer co-extrusion die head of the three-layer co-extrusion extruder according to a preset extrusion ratio of the inner layer material, the middle layer material and the outer layer material to form a three-layer co-extruded tubular sheath; The three-layer co-extruded tubular sheath is introduced into a cooling water tank with the water temperature controlled at 15-25°C. After cooling and shaping, it is towed by a traction device and cut into the required length to obtain a finished flame-retardant sheath tube for power cables.
10. The preparation method according to claim 9, characterized in that: The preset extrusion ratio of the inner layer material, the middle layer material and the outer layer material is 1:2:1.